Journal of international women's studies - Bridgewater State College (Bridgewater, Mass. : Bridgewater State College, 1999)
This journal provides a forum to explore the relationship between feminist theory and various forms of organizing.
Title from index screen (viewed May 3, 2002).
Mode of access: World Wide Web.
Latest issue consulted: Vol. 5, #1 (Nov. 2003) (viewed Jan. 23, 2004).
Keywords: Women's studies -- Periodicals; Women's rights -- Periodicals; Feminism -- Research -- Periodicals; Women -- Research -- Periodicals; Feminism -- Research; Women -- Research; Women's rights; Women's studies; Gender Studies & Sexuality; Electronic journals